(untitled) (Journal of Kidney Cancer, 2024)
Central nervous system hemangioblastoma (CNS-HB) is the most common manifestation of von Hippel–Lindau disease (VHL). The main axis of the CNS-HB pathway is the VHL-HIF signaling pathway. Recently, we proposed an alternative VHL-JAK-STAT pathway in CNS-HB. In contrast, the VHL substrate transcription factor zinc fingers and homeoboxes 2 (ZHX2) have been identified as the oncogenic drivers in VHL-deficient clear cell renal cell carcinoma (RCC). However, ZHX2 expression in CNS-HB has not been previously reported. Furthermore, the VHL-ZXH2-NF-κB signaling pathway in CNS-HB remains unresolved. In this study, we aimed to investigate ZHX2 expression and VHL gene alteration in CNS-HB and propose the role of ZHX2 in CNS-HB. Using the MACS method, Scl+ hemangioblastoma-like cells were isolated from multipotent nestin-expressing stem cells. The ubiquitination of ZHX2 in these cells and the immunoprecipitation between ZHX2 and VHL were investigated. In addition, the VHL genes of patients with hemangioblastoma were analyzed. ZHX2 expression in CNS-HB tissues was examined by immunohistochemistry and western blotting. In addition, VHL gene mutations in CNS-HB were analyzed by sequencing. The association between ZHX2 expression and VHL gene mutation was analyzed. ZHX2 was ubiquitinated in Scl+hemangioblastoma-like cells after the transfer of the VHL expression vector into these cells. ZHX2 expression in these cells was well detected before transfer but disappeared after the transfer. ZHX2 expression was detected in 18 of the 21 CNS-HB tissues by immunoblotting and/or immunohistochemistry. Sporadic CNS-HB showed weak expression, whereas VHL-related CNS-HB showed moderate or strong expression. In particular, CNS-HB with severe VHL gene mutations, including large deletions, showed strong or moderate ZHX2 expression. The association between VHL gene mutation and ZHX2 expression revealed a significant correlation between VHL gene alteration severity and the level of immunoblotting (P < 0.05). In conclusion, the severity of VHL gene alteration correlates with the level of ZHX2 expression. ZHX2 is predominantly expressed in CNS-HB, especially in VHL-related cases with severe VHL gene alterations, suggesting a potential role in tumorigenesis and proliferation of CNS-HB.